Identification of recurrent regulated alternative splicing events across human solid tumors. Issue 10 (23rd April 2015) - Danan-Gotthold, Miri; Golan-Gerstl, Regina; Eisenberg, Eli; Meir, Keren; Karni, Rotem; Levanon, Erez Y.
Abstract: Cancer is a complex disease that involves aberrant gene expression regulation. Discriminating the modified expression patterns driving tumor biology from the many that have no or little contribution is important for understanding cancer molecular basis. Recurrent deregulation patterns observed in multiple cancer types are enriched for such driver events. Here, we studied splicing alterations in hundreds of matched tumor and normal RNA-seq samples of eight solid cancer types. We found hundreds of cassette exons for which splicing was altered in multiple cancer types and identified a set of highly frequent altered splicing events. Specific splicing regulators, including RBFOX2, MBNL1/2 and QKI, appear to account for many splicing alteration events in multiple cancer types. Together, our results provide a first global analysis of regulated splicing alterations in cancer and identify common events with a potential causative role in solid tumor development.